(untitled) (LEARNing Landscapes, 2014)
The terms "reflection" and "reflective practice" occur frequently in educational research and practice, particularly in numerous course descriptions for pre-service teacher education. However, the author remains unconvinced we, as teacher educators, are always accomplishing what we think and/or say we are in the name of "reflection." This article seeks to promote further dialogue around the role of reflection in teacher education via explorations of what more can be learned, while underscoring the need to clarify understandings in this complex area. The author draws on her own experiences as a reflective practitioner and advocate for the promotion of meaningful reflection as professional learning.